Synthesis and reactions of (Z)-2-imino-5-(3,4,5-trimethoxy benzylidene)thiazolidin-4(H)one - Mahmoud, Mahmoud Refaee; Madkour, Hassan Mohamed Fawzy; El-Bordany, Eman Abd El-Fattah; Soliman, El-Sayed Ahmed (European Journal of Chemistry, 2011)
5-Arylmethylene-2-imino-4-oxo-2-thiazolidine 3 was obtained as the sole product from the reaction of α-cyano-3,4,5-trimethoxy cinnamonitrile and/or ethyl-α-cyano-3,4,5-trimethoxy cinnamate (1a,b) with 2-imino-4-oxo-2-thiazolidine 2. The reaction of 3 with benzyl amine gave the imidazolidin-4(H)one derivative 4 while with hydrazine hydrate afforded the dimeric product 5. Also, reaction of thiazolidinone derivative 3 with piperidine gave thiazol-4(5H)one derivative 6 which on treatment with Grignard reagent and active methylene compounds afforded thiazolidin-4-one derivatives 7-9, respectively. Compound 6 was converted to the potassium salt 10 which treated with acetic acid, ethyl chloroacetate and furoyl chloride to give the compounds 11-13, respectively. The structures of all new compounds were evidenced by microanalytical data and spectral data.